Deprotection of silyl ethers by using SO3H silica gel: Application to sugar, nucleoside, and alkaloid derivatives. Issue 36 (7th September 2017) - Fujii, Hideaki; Shimada, Naoyuki; Ohtawa, Masaki; Karaki, Fumika; Koshizuka, Masayoshi; Hayashida, Kohei; Kamimura, Mitsuhiro; Makino, Kazuishi; Nagamitsu, Tohru; Nagase, Hiroshi
Abstract: We applied a desilylation procedure using SO3 H silica gel, with the surface modified by alkylsulfonic acid groups, to silylated sugar, nucleoside, and alkaloid derivatives. The treatment with SO3 H silica gel provided desilylated products in good to excellent yield. In the reactions of sugar and nucleoside derivatives, no silyl residue was detected in the crude products, but the crude products of the reaction of alkaloids contained small amounts of silyl residues. Even though the sugar and nucleoside derivatives had a labile glycosyl and CN bond, respectively, these bonds tolerated the reaction conditions. These outcomes suggested that the desilylation procedure using SO3 H silica gel would be applicable to the deprotection of a variety of types of compounds protected by silyl groups. In a gram scale experiment, the desilylation procedure successfully proceeded without the observation of any silyl residue in the crude product. Graphical abstract: